2007
DOI: 10.1016/j.neuroscience.2007.01.056
|View full text |Cite
|
Sign up to set email alerts
|

The parkinsonian neurotoxin rotenone activates calpain and caspase-3 leading to motoneuron degeneration in spinal cord of Lewis rats

Abstract: Exposure to environmental toxins increases the risk of neurodegenerative diseases including Parkinson's disease (PD). Rotenone is a neurotoxin that has been used to induce experimental Parkinsonism in rats. We used the rotenone model of experimental Parkinsonism to explore a novel aspect of extra-nigral degeneration, the neurodegeneration of spinal cord (SC), in PD. Rotenone administration to male Lewis rats caused significant neuronal cell death in cervical and lumbar SC as compared with control animals. Dyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 74 publications
(99 reference statements)
5
68
0
1
Order By: Relevance
“…The involvement of reactive astrocytosis in rotenoneinduced neurotoxicity has also been suggested [45]; therefore, the expression of reactive astrocytes was also assessed by estimating the level of GFAP. Rotenone administration caused significantly increased protein level of GFAP in both STR and MB regions after rotenone administration which was supported with the GFAP immunoreactivity observation (supplementary data, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of reactive astrocytosis in rotenoneinduced neurotoxicity has also been suggested [45]; therefore, the expression of reactive astrocytes was also assessed by estimating the level of GFAP. Rotenone administration caused significantly increased protein level of GFAP in both STR and MB regions after rotenone administration which was supported with the GFAP immunoreactivity observation (supplementary data, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…22 We conclude that AIF is involved in MPP+-induced cell death, because an antisense ODN that inhibits its expression caused a significant increase in the survival of treated PC12 and PC139 cultures, although increased survival was not seen in cultures given MPP+ together with the control (sense) ODN, which does not inhibit AIF expression. Release is due to calpain activation, as evidenced by the findings that (1) MPP+ increased the p76/p80 ratio of the calpain I forms, 24,28,29 and (2) both AIF release and PCD (TUNEL) were inhibited by the broad-spectrum calpain inhibitor calpeptin. Calpeptin inhibited the MPP+-induced increase in the p76/p80 ratio in PC12 and PC139 cells (data not shown), as also independently reported for its effect on p76/p80 in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for neuronal degeneration characteristic of PD is still poorly understood and appears to involve multiple death programs. They include activation of caspases 19,28,37 or calpain, 7,28 mitochondrial dysfunction and increased release of proapoptotic factors, such as cytochrome c and AIF, 5,7 as well as Bax upregulation and its translocation to the mitochondria. 25,35,37 Overexpression of Bcl-2 6,35,38 or Hsp70 9 was shown to contribute to protection.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular and animal models using environmental and biological toxins, especially lipopolysaccharides (LPS), herbicides and pesticides like rotenone or MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine), can induce both astrogliosis and microgliosis, which is accompanied by neuronal death, mitochondrial dysfunction and nuclear fragmentation [41][42][43][44][45]. Additionally, it was previously shown that the injection of LPS in rat brains was followed by an increase in the inducible nitric oxide synthase (iNOS; EC 1.14.13.39), suggesting that chronic glial activation can cause oxidative stress in the brain, similarly to that seen in neurodegenerative processes like AD and Parkinson [10,39,45].…”
Section: Astrogliosis and Parkinsonmentioning
confidence: 99%